Pendidikan Agama Kristen Sebagai Sarana Membangun Persatuan di Tengah Keragaman - Rupina Rupina; Sumiati Titi; Yunriana Sartika Mesah; Semuel Linggi Topayung (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This article examines the role of Christian religious education in Indonesia as a tool for creating unity amidst the diversity of society. With a long history of forming character and positive values, this education needs to adapt to the context of advanced society. Through emphasizing the values ​​of tolerance, interfaith dialogue, and character development, Christian Religious Education aims to reduce tensions between various religious groups. This article also highlights the contribution of education in social activities and community service that supports social and economic development. In facing the challenges of globalization, education must continue to innovate by utilizing technology to instill inclusive values. In conclusion, Christian religious education not only functions to educate individuals, but also as an agent of social change, creating a society that is more united and harmonious in diversity.